Relationship between cash holdings and expected equity returns: Evidence from Pacific alliance countries - Judith Vergara Garavito; Sergio J. Chión (Journal of Economics, Finance and Administrative Science, 2021)
Purpose: This paper aims to examine the relationship between cash holdings (CH) and expected equity return in a sample of firms of Pacific alliance countries. Design/methodology/approach: This paper constructed a panel of Pacific alliance firms for the period ranging from 2010 to 2016. This paper estimated different specification models using multivariate regression, and the statistical technique used to validate the hypothesis was panel data. Findings: Results showed that there is a positive relationship between CH and expected equity return (r). The relationship between CH and systematic risk (ß) was estimated and this paper found a positive and statistically significant association. Findings suggest that corporate liquidity contains underlying information that contributes to explain the expected equity return, which, if ignored, can produce quite misleading results. Originality/value: The results of this study have both academic and practical implications. First, the findings of the research contribute to a better understanding of the asset pricing models in emerging countries. On the other hand, the results obtained in this study can serve shareholders to make better estimations of the expected equity return, so investors can improve the risk-return trade-off due to the model allow a better estimation of the risk-return relation.
Keywords: 330; Cash holdings; Emerging countries; Expected equity return; Systematic risk